2009
DOI: 10.1007/s00404-009-1196-8
|View full text |Cite
|
Sign up to set email alerts
|

Does amnioinfusion reduce caesarean section rate in meconium-stained amniotic fluid

Abstract: Transcervical amnioinfusion in labour for meconium-stained amniotic fluid is a simple, safe and easy-to-perform procedure. It can be performed safely in a setup with limited peripartum facilities, especially in developing countries, to decrease intrapartum operative intervention and reduce foetomaternal morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…Choudhary, Bano (2010) also reported shorter duration of NICU stay (4.45±3.46 days) in study group as compared to control group (7.24±4.11 days). 24 The findings in present study highlighted the role of aminoinfusion in reducing the caesarean rate, improving neonatal Apgar, reducing respiratory distress leading to lesser need of neonatal resuscitative measures and reduced neonatal morbidity. These findings are encouraging and provide evidence that even in wellequipped facilities aminoinfusion plays an important role in reducing caesarean rates and neonatal morbidity.…”
supporting
confidence: 54%
“…Choudhary, Bano (2010) also reported shorter duration of NICU stay (4.45±3.46 days) in study group as compared to control group (7.24±4.11 days). 24 The findings in present study highlighted the role of aminoinfusion in reducing the caesarean rate, improving neonatal Apgar, reducing respiratory distress leading to lesser need of neonatal resuscitative measures and reduced neonatal morbidity. These findings are encouraging and provide evidence that even in wellequipped facilities aminoinfusion plays an important role in reducing caesarean rates and neonatal morbidity.…”
supporting
confidence: 54%
“…These findings go in hand with Regi et al (16) who found AI was a beneficial therapeutic intervention in women patients showing fetal distress in first stage of labor, and it reduced CS for fetal distress. Choudhary et al (17) who found AI during labor was not associated with any significant maternal complications, but was associated with a statistically significant reduction in CS incidence than in control women (31 vs. 61%). Also, Butt & Ahmed (18) reported that transabdominal AI is a useful procedure to reduce complications that result from oligohydramnios as AI increases the latency period, and may result in better perinatal outcome by improving birth weight.…”
Section: Results:-mentioning
confidence: 92%
“…Also, Choudhary et al (17) reported that AI during labor was not associated with any significant neonatal complications, but was associated with improved neonatal outcome as evidenced by statistically improved Apgar score at 1 min in newborns of women of study versus control group (10 vs. 37.2%). Moreover, Bansal et al (19) detected significantly lower frequency of respiratory distress of neonate of women received AI than in control group (4% vs. 12 %).…”
Section: Results:-mentioning
confidence: 97%
“…The neonatal death in the study group was 1 and that in the control group was 3 and statistically it wasn't significant. Amnioinfusion is associated with substantive improvements in perinatal outcome only in settings where facilities for perinatal surveillance are limited 11 . The mechanism of benefit is not clear as it is due to dilution of meconium or relief of oligohydramnios.…”
Section: Resultsmentioning
confidence: 99%